Search for time-dependent 𝐶⁢𝑃 violation in 𝐷0→𝜋+⁢𝜋−⁢𝜋0 decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Glaser, Fabian; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; et al. (Physical review letters, 2024)
A measurement of time-dependent 𝐶⁢𝑃 violation in 𝐷0→𝜋+⁢𝜋−⁢𝜋0 decays using a 𝑝⁢𝑝 collision data sample collected by the LHCb experiment in 2012 and from 2015 to 2018, corresponding to an integrated luminosity of 7.7 fb−1, is presented. The initial flavor of each 𝐷0 candidate is determined from the charge of the pion produced in the 𝐷*⁢(2010)+→𝐷0⁢𝜋+ decay. The decay 𝐷0→𝐾−⁢𝜋+⁢𝜋0 is used as a control channel to validate the measurement procedure. The gradient of the time-dependent 𝐶⁢𝑃 asymmetry Δ⁢𝑌 in 𝐷0 →𝜋+⁢𝜋−⁢𝜋0 decays is measured to be Δ⁢𝑌=(−1.3±6.3±2.4)×10−4, where the first uncertainty is statistical and the second is systematic, which is compatible with 𝐶⁢𝑃 conservation.